Thomas Aquinas's Understanding of Prayer in the Light of the Doctrine of Creatio Ex Nihilo. (25th March 2013) - te, Rudi
Abstract This article discusses Thomas Aquinas's view on the 'utility' of prayer in the light of the doctrine of creation ex nihilo. 'Creatio ex nihilo' means, among other things, that nothing can exist that is not caused by the universal power of God. The universal causality of creation implies that God cannot receive from the world or react to any activity on our part. This claim of divine immutability throws into question the intelligibility of prayer: does it make sense to pray to God when his providence is certain and immutable? I argue that the God Thomas conceives is not the God of the ancient régime, the sovereign deity of absolute power who is in charge of everything; on the contrary, it is a God who grants the secondary causes within the world their own power and operation. The human activity of prayer belongs to this sphere of 'second causes', through which God realizes his providential plan. God's providence provides good things to us, one of which is the fulfillment of our prayers.